PREFORMULATION AND DEVELOPMENT OF CURCUMIN MAGNETIC NANOSUSPENSION USING MAGNETITE (Fe3O4) AND METHYL CELLULOSE - J. MUTHU MOHAMED; P. BHARATHIDASAN; M. MOHAMED RAFFICK (International Journal of Pharma and Bio Sciences, 2012)
This work aims at the preformulation and development of intra-articular drug delivery system by enhancing the release of curcumin from curcumin magnetic nanosuspension for the management of rheumatoid arthritis. The preformulation studies such as solubility, incompatible studies of drug, magnetite and polymer with various stress conditions, LOD, particle size, hygroscopicity and thermal properties were carried out. The results give evidence that curcumin was absolutely suitable for the development of magnetic nanosuspension. Magnetite (Fe3O4) and methyl cellulose has been used for the preparation of magnetic nanosuspension using the solvent displacement method. Physiochemical characterization of CMNS was carried out to obtain information about particle size distribution, drug loading efficiency, morphology, pH, viscosity, density, sedimentation rate, magnetic susceptibility test, assay and release was found from in vitro dissolution studies using 0.01N hydrochloric acid with 0.8% SLS at 370C ± 0.50C. Curcumin release from magnetic nanosuspension of selected formulations (F6) show better release with external magnetic fields among other formulations (F1 – F5).